TEXTBOOK EVALUATION BASED ON THE CONTENT STANDARD OF BSNP: A SURVEY STUDY ON TEACHERS’ PERCEPTION IN SENIOR HIGH SCHOOLS IN MUSI RAWAS REGENCY - Rusdin Rusdin (ELTE Journal (English Languange Teaching and Education), 2014)
ABSTRACT The problems of the study are: 1) What are the content standards of BSNP for the School Based Curriculum contained in the English textbook used by the eleventh year students of Senior High School? and 2) What are the teachers’ perceptions of the Senior High School textbooks?. The objectives of the study are: 1) to find out  what the content standard of BSNP for the School Based Curriculum are contained in the English textbook used by the eleventh year students of Senior High School, and 2) to find out the teachers’ perceptions of the Senior High School textbooks. The method of the research was survey method follows the principles of qualitative-quantitative approach. While the technique for collecting the data was through questionnaire, observation and documentation forms. Then, the technique for analyzing the data was through determining the criteria for the textbook evaluation, then analyzed them using scoring system afterwards, assessing the experts’ perceptions in term of rating scale to see the percentages of the judgments of the textbooks used. The results of the study showed that the content standard of BSNP for School Based Curriculum were implemented around 53.50 and average 79% in Developing English Competencies, while in Interlanguage that the content standard of BSNP for School Based Curriculum were implemented around 51, 81, and average 76% and Look a head that the content standard of BSNP for School Based Curriculum were implemented around 53.50 and average 79%. In line with teachers’ perceptions of what the textbooks, it was found out that the three textbooks, Developing English Competencies, Interlanguage and Look A Head were categorized and implemented in good perception in terms of positive aspects of the criteria of textbooks. In conclusion, the average of the three textbooks, namely: Developing English Competencies got score 78,60%, while Interlanguage got score 71,72% and Look A Head got score 73,20%. In this way, and they were considered “good”. Keywords: Textbook Evaluation, Content Standard, BSNP, Survey Study